Minimal invasive extracorporeal circulation preserves platelet function after cardiac surgery: a prospective observational study. (March 2020) - Argiriadou, Helena; Antonitsis, Polychronis; Gkiouliava, Anna; Papapostolou, Evangelia; Deliopoulos, Apostolos; Anastasiadis, Kyriakos
Introduction: Cardiac surgery on conventional cardiopulmonary bypass induces a combination of thrombocytopenia and platelet dysfunction which is strongly related to postoperative bleeding. Minimal invasive extracorporeal circulation has been shown to preserve coagulation integrity, though effect on platelet function remains unclear. We aimed to prospectively investigate perioperative platelet function in a series of patients undergoing cardiac surgery on minimal invasive extracorporeal circulation using point-of-care testing. Methods: A total of 57 patients undergoing elective cardiac surgery on minimal invasive extracorporeal circulation were prospectively recruited. Anticoagulation strategy was based on individualized heparin management and heparin level–guided protamine titration performed in all patients with a specialized point-of-care device (Hemostasis Management System – HMS Plus; Medtronic, Minneapolis, MN, USA). Platelet function was evaluated with impedance aggregometry using the ROTEM platelet (TEM International GmbH, Munich, Germany). ADPtest and TRAPtest values were assessed before surgery and after cardiopulmonary bypass. Results: ADPtest value was preserved during surgery on minimal invasive extracorporeal circulation (58.2 ± 20 U vs. 53.6 ± 21 U; p = 0.1), while TRAPtest was found significantly increased (90 ± 27 U vs. 103 ± 38 U; p = 0.03). Postoperative ADPtest and TRAPtest values were inversely related to postoperative bleeding (correlation coefficient: −0.29; p = 0.03 for ADPtest and correlation coefficient: −0.28; p = 0.04 for TRAPtest). The preoperative use of P2Y12 inhibitors was identified as the only independent predictor of a low postoperative ADPtest value (OR = 15.3; p = 0.02). Conclusion: Cardiac surgery on minimal invasive extracorporeal circulation is a platelet preservation strategy, which contributes to the beneficial effect of minimal invasive extracorporeal circulation in coagulation integrity.